PENERAPAN STRATEGI PEMBELAJARAN AKTIF ROLLED UNTUK MENINGKATKAN HASIL BELAJAR SISWA IPA FISIKA KELAS VII SMPN 40 PEKANBARU - Een Eka Putri; Hendar Sudrajad; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: The purpose of this research is to describe students’ learning result by using learning active strategy of Rolled. The type of this research was a pre- experimental research, with design of Intact- Group Comparison. The populations of this research were seven grade students of junior high school 40 Pekanbaru which total number were 176 students. The writer took 2 classes as the sample by using random-sampling technique which was using lottery to decide control class and experimental class. The data on this research is in form of students’ scores taught by using learning active strategy of Rolled and it is analyzed on descriptive and inferential. The result of the research shows that there is a difference on students’ learning achievement between experimental class and control class. Students’ comprehension taught by using learning active strategy of Rolled was 72, 16 % and students’ comprehension taught by using conventional strategy was 61, 14%. Based on the data, can be concludes that learning active strategy of Rolled improves students learning result in physics on science at the seven grade students’ of junior high school 40 Pekanbaru.